ACCOMMODATING THE NATIONAL EDUCATION POLICY IN PONDOK PESANTREN DDI MANGKOSO: STUDY PERIOD OF 1989-2018 - Muhammad Alqadri Burga; Azhar Arsyad; Muljono Damopolii; A. Marjuni (Islam Realitas: Journal of Islamic and Social Studies, 2019)
AbstractThis research was aimed at analyzing the 1) existence of the Pondok Pesantren DDI Mangkoso as a traditional Islamic educational institution; 2) the dynamic policy of national education in the period of 1989-2018; 3) various national education policy accommodating by the Pondok Pesantren DDI Mangkoso; and 4) varied obstacles and experienced by the pesantren in accommodating national education policy and the solutions. The results of this research show that the Pondok Pesantren DDI Mangkoso is still kept existing as a traditional Islamic educational institution by preserving five roles: a place transforming classical Islamic sciences, Da’wah institution, Islamic tradition conservationists, Islamic scholar generating center, and community service and empowerment. The position change of pesantren in the national educational policy during 1989 – 2018 implicates dynamiclally to the Pondok Pesantren DDI Mangkoso. The accommodation forms of national education policy conducting by the Pondok Pesantren DDI Mangkoso are classical system, national education curriculum implementation, and standardizing the learning process and educators. Some obstacles facing in accommodating these forms are like culture and organizational structure wrestling, limited resource, and lack of community participation. This research has implications for the importance of the accumulation of cultural values, religious values, and modern values in pesantren so that it can compete amid the progress of educational institutions in general Penelitian ini bertujuan untuk menganalisis 1) eksistensi Pondok Pesantren DDI Mangkoso sebagai representasi lembaga pendidikan Islam tradisonal; 2) dinamika kebijakan pendidikan nasional kurun waktu 1989-2018; 3) ragam kebijakan pendidikan nasional yang diakomodasi oleh Pondok Pesantren DDI Mangkoso; dan 4) ragam hambatan Pondok Pesantren DDI Mangkoso dalam mengakomodasi kebijakan pendidikan nasional beserta solusinya. Metode penelitian yang digunakan adalah kualitatif dengan pendekatan fenomenologi. Hasil penelitian menunjukkan bahwa Pondok Pesantren DDI Mangkoso tetap eksis sebagai lembaga pendidikan Islam tradisional meski melakukan pengembangan yang sifatnya modern dengan mempertahankan lima peran, yaitu: Tempat transmisi ilmu-ilmu Islam klasik, lembaga dakwah, pelestari tradisi Islam, pusat reproduksi ulama, serta tempat pengabdian dan pengembangan masyarakat. Perubahan posisi pesantren dalam kebijakan pendidikan nasional kurun waktu 1989-2018 berimplikasi terhadap kebijakan pendidikan Pondok Pesantren DDI Mangkoso yang dinamikanya dibagi ke dalam tiga tahap, yaitu: transformasi kelembagaan, pemaduan kurikulum, dan penerapan paradigma inklusif berbasis budaya. Berbagai hambatan dalam akomodasi tersebut adalah pergumulan kultur dan struktur organisasi, keterbatasan sumber daya, dan minimnya partisipasi masyarakat. Penelitian ini berimplikasi pada perlunya akumulasi nilai tradisional, nilai agama, dan nilai modern oleh pesantren agar mampu bersaing bahkan menjadi inspirasi di tengah kemajuan lembaga pendidikan pada umumnya.